Red Beet Extract Powder, Gelatin and Sucrose Interactions in Gummy Candies - Toker, Omer Said; Atalar, Ilyas; Kurt, Abdullah; Palabiyik, Ibrahim; Konar, Nevzat (MDPI, 2025)
Gummy candies rely on sugar, gelatin, and synthetic colorants, but rising demand for natural alternatives makes replacement essential. Interactions between natural additives and main components (gelatin, sucrose), especially their effects on color and texture, remain unclear. This study examines the existence and amounts of sucrose, gelatin, and natural coloring agent, red beetroot extract powder (RBEP), in gummy candy compositions, along with main quality attributes and stability behavior. The effects of these variables on the main physicochemical, color, texture and bioactive properties were investigated. Model gummy samples' hardness (10.68-19.18 N), resilience (0.57-0.89), cohesiveness (0.87-1.01), springiness (0.19-0.54 mm), gumminess (9.63-21.30 N), and chewiness (2.15-8.29 N x mm) properties were determined by texture profile analysis. The values of L*, a*, b*, chroma, and hue angle were determined in the ranges of 23.9-91.5, (-0.93)-43.6, 1.06-8.17, 6.20-44.0, and 5.97-97.4, respectively. The interactions between RBEP x gelatin and RBEP x sucrose were found to be effective in color parameters. Total phenolic content (TPC) values and inhibition values for antioxidant activity (AA, % inhibition) ranged from 25.6 to 257.4 mg GAE/kg and 0.00-49.8%, respectively. The optimum composition, determined by considering texture properties and stability behavior as the response, revealed the concentrations of sucrose, gelatin solution, and RBEP as 34.53 g/100 g, 18.33 g/100 g, and 0.44 g/100 g, respectively. The study is the first to investigate the effect of RBEP concentration on the quality parameters of gummy candies and interactions with other components of the formulation. The results will raise awareness about the use of colorants in the confectionery industry and contribute to developing novel products.
Keywords: confectionery; gelatin; sucrose; colorant; optimization; MODEL SYSTEM; SUGAR; MOISTURE; CRYSTALLIZATION; ANTHOCYANINS; ISOMALTULOSE; POLYPHENOLS; FORMULATION; STABILITY; TEXTURE; Food Science & Technology